The role of sociodemographic and clinical factors in the initiation and discontinuation of attention deficit hyperactivity disorder medication among young adults in Sweden - Gémes, Katalin; Taipale, Heidi; Björkenstam, Emma; Rahman, Syed; Gustafsson, Klas; Tanskanen, Antti; Ekselius, Lisa; Mittendorfer-Rutz, Ellenor; Helgesson, Magnus (Frontiers in Psychiatry, 2023)
Introduction: Long-term medication use is a recommended treatment for attention-deficit/hyperactivity disorder (ADHD), however, discontinuation is common. Non-medical factors which might influence initiation and discontinuation are understudied. Therefore, we investigated how different sociodemographic factors and comorbidities were associated with the initiation and discontinuation of ADHD medication use among young adults. Methods and Results: We conducted a population-based prospective cohort study using individually linked administrative register data, in which we included all individuals residing in Sweden, between the age of 19 and 29 who were first diagnosed with ADHD between January 2006 and December 2016 (n=59,224). ADHD medication initiation was defined as the first prescription of ADHD medication in the period from three months before to six months after the cohort entry date. Those who initiated ADHD medication were followed up for medication use until discontinuation, death/emigration, or until 2019. Logistic and Cox regression models were used to investigate the associations between sociodemographics, health-related predictors and initiation, as well as discontinuation. Overall, 48.7% of the 41,399 individuals initiated ADHD medication, most often methylphenidate (87%). Among the initiators, 15,462 (77%) discontinued medication use during the follow-up (median time: 150 days). After mutually adjusting all other predictors, initiation was positively associated with older age, male sex, higher level of education, and negatively associated with living at home with parents, immigrant status, being unemployed during the year before inclusion, being on disability pension, having autism, substance use, schizophrenia-spectrum disorders, other mental disability/developmental disorders, cardiovascular diseases or previous accidents. Discontinuation was positively associated with being born abroad, living in big cities, being unemployed during the year before inclusion, having cancer, and negatively associated with a higher educational level, having depression, anxiety or stress-related disorder, autism spectrum disorder or diabetes. Conclusions: Besides medical factors, sociodemographics, such as educational attainment and immigrant status might also play a role in the initiation and discontinuation of ADHD medication use among young adults newly diagnosed with ADHD.